2015
DOI: 10.1086/680670
|View full text |Cite
|
Sign up to set email alerts
|

To Know and to Care: How Awareness and Valuation of the Future Jointly Shape Consumer Spending

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 155.69.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 49 publications
1
73
2
Order By: Relevance
“…Our conclusions are related to work on consideration of opportunity costs (Bartels and Urminsky 2015;Frederick et al 2009;Spiller 2011) and earmarking (Cheema and Soman 2011;Webb and Spiller 2014). These research streams examine how potential uses of money-spontaneously generated or provided-influence spending decisions.…”
Section: Discussionmentioning
confidence: 83%
“…Our conclusions are related to work on consideration of opportunity costs (Bartels and Urminsky 2015;Frederick et al 2009;Spiller 2011) and earmarking (Cheema and Soman 2011;Webb and Spiller 2014). These research streams examine how potential uses of money-spontaneously generated or provided-influence spending decisions.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, it is not clear whether the ASOC effect is due to changes in awareness of the SS opportunity cost (as we emphasize in this paper), changes in evaluations of the SS opportunity cost (e.g., perhaps people are naturally aware of it, but highlighting it makes them care more about it), or both (see Bartels and Urminsky 2015). The choice time data we reported suggest that the SS zero (or SS nothing reminder) makes information more salient to decision makers, which supports the awareness account.…”
Section: Discussionmentioning
confidence: 92%
“…the non-presented options: opportunity costs). The importance of considering opportunity costs was further demonstrated by Bartels and Urminsky (2015). They found that valuing future outcomes highly is only related to decreased spending when people consider opportunity costs.…”
Section: Opportunity Costsmentioning
confidence: 99%